Nematode Parasitism III Sheep Production - Liu, S M; Karlsson, L J F (Annals of Arid Zone, 2016)
Gastro-intestinal nematodes cause widespread health problems in the sheep industry with substantial economic losses involving the expenditure on treatment of infected animals, loss of productivity and deaths. The control of nematodes is currently based largely on treatment with anthelmintics. A high reliance on anthelmintic 1.:ontrol has resulted in strong selection for anthelmintic resistance in the target parasite populations and is becoming a significant threat to the sustainability and profitability of the sheep industry. Therefore, there is an urgent need to develop sustainable nematode control systems. Genetic selection strategies against parasitism have a long-term effect and cumulative gains, and have significantly reduced the contamination of worm eggs on pastures. Generally genetic resistance against nematodes has clear benefits in weight gain during infection, but less for wool growth particularly in young lambs, possibly because both the immune responses to infection and wool growth compete for specific nutrients. The relationships between the resistance and production traits may change depending on sheep breeds. Parasitism-associated diarrhea is another genetic trait with a low to medium heritability as well as a genotype by environment interaction, and requires new approaches to overcome this problem. Attention to optimize nutrition strategies for parasitized sheep are required to recover the loss of productivity associated with the infection. In young growing animals, the benefits may also be extended to improve the development of their lifetime immune competency, while in reproductive ewes protein supplementation is required to minimize the periparturient relaxation of immunity if grazing nutrient intake does not meet the very high demands for protein during this period. Pastures that contain high levels of condensed tannins can increase the by-pass protein and essential amino acid supplies to the host, and ameliorate nutritional and/or immunological status of the host. They also have direct antiparasitic effects on development of larvae, fecundity of the worms and worm viability in the gastrointestinal tract. These approaches should be integrated in an optimum way based on local circumstances. so a sustainable nematode control system can be developed.